2019
DOI: 10.1038/s41598-019-43526-7
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Surface Silver Nano-network Structures through Hot Electron Regulated Diffusion-limited Aggregation

Abstract: A surface Ag nano-network pattern is formed by first depositing Ag nanoparticles (NPs) on a conductive template, which has a certain defect structure, and then illuminating the Ag NPs with ultraviolet (UV) light in a moist environment. Such an Ag nano-network pattern consists of multiple connected Brownian trees (BTs), which are produced through the diffusion-limited aggregation (DLA) process. In the DLA process, diffuse Ag + ions, which are generated by UV light illumination and dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Further study should also lead to the application to flexible optoelectronics. Different from our previous work, in which all the original Ag NPs were reorganized, either dissolved, merged, or enlarged, to form an NNW structure, the composition of AgO x in an NNW structure of the current study results in the advantage of high thermal stability. The coverage of AgO x on an NNW structure can also help in the resistance to sulfidation, further oxidation, and other corrosion effects.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Further study should also lead to the application to flexible optoelectronics. Different from our previous work, in which all the original Ag NPs were reorganized, either dissolved, merged, or enlarged, to form an NNW structure, the composition of AgO x in an NNW structure of the current study results in the advantage of high thermal stability. The coverage of AgO x on an NNW structure can also help in the resistance to sulfidation, further oxidation, and other corrosion effects.…”
Section: Discussionmentioning
confidence: 72%
“…Such an NNW structure could be formed at room temperature and had the potential for the application to flexible optoelectronics. The fabrication of such an NNW structure required the following conditions: (1) UV light (>360 nm in wavelength) illumination onto the surface Ag NPs for generating hot electrons through intraband-related absorption, (2) Ag NPs on a slightly conductive template for hot electron migration, and (3) ambient moisture to produce a condensed surface water layer (a couple nm in thickness) for dissolving Ag + ions such that DLA can occur. The sheet resistance and transparency of such a surface Ag NNW structure depended on the deposited Ag thickness at the beginning of fabrication . Usually, a thicker (thinner) Ag deposition led to lower (higher) sheet resistance and lower (higher) transparency.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 However, a Ag nanonetwork (NNW) with multiple connected Brownian trees (BTs) shows high transparency in these spectral ranges. 4 It has been reported that a Ag-nanowire (NW)-based NNW transparent conductor can be fabricated by piling up Ag NWs and welding their intersections to form a network structure. 5,6 Thus, the Ag NNWs have a potential application in flexible optoelectronics fields as a transparent conductor with low sheet resistance and high transparency.…”
Section: Introductionmentioning
confidence: 99%